Conjugate numerical analysis on bundle effects for integrated heat transfer of LNG ambient air vaporizer. (5th November 2020) - Liu, Shanshan; Jiao, Wenling; Zhang, Ping
Highlights: An integrated numerical model of ambient air vaporizer (AAV) considering the conjugate heat transfer was proposed and validated by experiments. The effects of the tube location in the AAV array on the heat transfer performance of each type of finned tube were investigated. The surrounding finned tube weakens the coordination of the flow and heat transfer. The circumferential local convective heat transfer coefficients decrease from 45° to 225° angular space and then arise from 225° to 360° angular space. Abstract: Ambient air vaporizer (AAV) is widely used to vaporize liquefied natural gas (LNG) in gas terminal stations due to its low cost in operating and eco-friendly advantages. Its vaporization efficiency depends on the overall heat transfer performance of the finned tube bundle, which was mostly represented by single tube in previous researches. This paper presented a numerical investigation on the integrated heat transfer of AAV tube bundle considering the heat transfer conjugate problem between different zones. An experimental test combined with the nondimensional correlation in finite space was conducted to validate the numerical model, and the results are in good agreement. The results indicate that the surrounding tubes weakens the field synergy of the flow and heat transfer in inner area of the AAV array, resulting in the decline of heat transfer coefficient from far to near the center of the array. For each finned tube in the AAV bundle, the circumferential local convective heat transfer coefficients decrease from 45° to 225° angular space and then arise from 225° to 360° angular space. Besides, poorer convective heat transfer of the air will lead to the delay of LNG multiphase flow with higher heat transfer intensity due to the conjugate heat transfer in AAV.